Juridical Review of the Problem of Extending Use Rights for Buildings Indicated to Be Abandoned (Case Study at PT Semen Gombong) - Andini, Marcelia Puspa; Suhadi, Suhadi (Annual Review of Legal Studies, 2024)
There is HGB land indicated as abandoned whose rights will expire in 2027. However, the community asked the Kebumen Regency Kantah and the Central Java BPN Regional Office not to extend the HGB land in the future. Until the author conducted research, the HGB land was still included in the land database indicated as abandoned. The problems studied in this research are: (1) What causes HGB land to be indicated as abandoned?  (2) What is the action of the Central Java BPN Regional Office regarding HGB land that is indicated to be abandoned? and (3) Can HGBs that are indicated to be abandoned be extended? This research uses a qualitative approach method with an empirical juridical research type.  The results of this research show that HGB land which is still included in the land database is indicated as abandoned because the land is not used according to its intended use and cannot be extended. The Central Java BPN Regional Office has carried out control over the HGB land but it has not been optimal due to obstacles related to the limited budget for controlling abandoned land. Then based on the research results related to HGB land and to optimize the stages of controlling abandoned land, the author proposes that HGB holders be able to carry out their obligations, namely utilizing and using the land according to the designation for granting rights, then it is proposed to increase cooperation between rights holders and related stakeholders in the granting process. the right to make decisions on HGB extensions and the need for an additional budget for the implementation of controlling abandoned land carried out by the Central Java BPN Regional Office.